Intellectual capital on Financial Performance: Sri Lankan Market - Pratheepkanth, P. (Uva Wellassa University, 2018)
The current theory of the firm posits that firms maximise their value by making decisions to maximise the wealth of their stakeholders. Intellectual capital is a key input to achieving that goal, is a major strategic asset capable of garnering sustainable competitive advantage. The data used in this study comes from 150 Sri Lanka (Colombo stock exchange listed firms). The research questions are answered via a quantitative research design that uses secondary data. This study finds that intellectual capital has a significant impact on ROA whereas the insignificant impact found between the intellectual and Tobin Q can be explained by other factors (e.g., Tobin Q may not handle the high levels of intangible assets present in rising knowledge economy of Sri Lanka) which validates the assertion that Sri Lankan culture may be more individualistic. Findings also demonstrate the Sri Lankan firms more closely adhere to the ethical branch of stakeholder theory.
Keywords: Intellectual capital; Financial performance; Sri Lanka